Covid-19 Dalam Perspektif Pengembangan Masyarakat Islam - Turasih Turasih (LP2M IAIN Syekh Nurjati Cirebon, 2022)
The Islamic Community Development is the implications of the concept of community development that emerged in response to the problems faced by human beings related to the development. From its history the islamic community development is a form of da'wah by deed (da'wah bil haal). The spirit of da'wah in community development is what characterizes the values of islamic goodness as an effort to overcome the problems that occur in society. As a perspective, the islamic community development can be used to capture the changes that occur in the community, especially in the face of the Covid-19 pandemic. The perspective of islamic community development also provides recommendations on adaptation and mitigation of the handling of Covid-19 by promoting islamic values sourced from the Qur'an and hadith.